2014
DOI: 10.1002/anie.201410067
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Azoimidazolium Dyes with Nitrous Oxide

Abstract: A new method for the synthesis of industrially important azoimidazolium dyes is presented. The procedure is based on a reagent which is rarely used in the context of synthetic organic chemistry: nitrous oxide ("laughing gas"). N2O is first coupled to N-heterocyclic carbenes. Subsequent reaction with aromatic compounds through an AlCl3-induced C-H activation process provides azoimidazolium dyes in good yields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
38
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 55 publications
(30 reference statements)
3
38
0
Order By: Relevance
“…[7] We were intrigued by the reaction of the strongly Lewis acidic phenyl cation with N 2 that affords the phenyldiazonium ion in cryogenic argon matrices, [8] and found that the planar C 6 H 5 + activates N 2 by greatly lowering its p*a cceptor orbital (LUMO:f rom 1.30 (N 2 )t oÀ6.24 eV; see Figure 1). [11] Surprisingly,t o date the corresponding azoammonium salts [RN 2 (NR 3 )][X] are unknown, [12] while the phosphine-diazonium Lewis adducts have been barely studied. NCoordination of diazonium salts to Lewis basic N-heterocyclic carbenes is well established and affords the strongly coloured, industrially produced azoimidazolium salts [RN 2 (NHC)][X] (X = Cl, BF 4 ,P F 6 ,e tc.).…”
Section: Themetal-freeactivationandfunctionalizationofdinitrogenmentioning
confidence: 99%
“…[7] We were intrigued by the reaction of the strongly Lewis acidic phenyl cation with N 2 that affords the phenyldiazonium ion in cryogenic argon matrices, [8] and found that the planar C 6 H 5 + activates N 2 by greatly lowering its p*a cceptor orbital (LUMO:f rom 1.30 (N 2 )t oÀ6.24 eV; see Figure 1). [11] Surprisingly,t o date the corresponding azoammonium salts [RN 2 (NR 3 )][X] are unknown, [12] while the phosphine-diazonium Lewis adducts have been barely studied. NCoordination of diazonium salts to Lewis basic N-heterocyclic carbenes is well established and affords the strongly coloured, industrially produced azoimidazolium salts [RN 2 (NHC)][X] (X = Cl, BF 4 ,P F 6 ,e tc.).…”
Section: Themetal-freeactivationandfunctionalizationofdinitrogenmentioning
confidence: 99%
“…113 These kinds of salts are of interest because they are strongly colored dyes. When the reactions are performed in the presence of an aromatic compound, azoimidazolium salts are formed in good yields (Scheme 19).…”
Section: N 2 O As N-atom Donormentioning
confidence: 99%
“…[1] Substituted azulenes have been employed in diverse contexts,i ncluding medicinal chemistry (as antiulcer, [2] antidiabetic, [3] anticancer, [4] antiarrhythmic, [5] and anti-erectile-dysfunction [6] agents,a nd as TXA 2 t receptor antagonists [7] ), solar cells, [8] metal-organic frameworks for hydrogen storage, [9] and organic electronics, [10] among others. [18] Alternatively,c ross-coupling methodologies should allow access to am uch wider range of substituted azulenes.T he reactivity described above suggests [15] Furthermore,t he ability to tune the absorption and emission maxima of azulenes by attaching conjugated substituents [16] has led to applications in bioimaging and fluorescence.…”
mentioning
confidence: 99%
“…[15] Furthermore,t he ability to tune the absorption and emission maxima of azulenes by attaching conjugated substituents [16] has led to applications in bioimaging and fluorescence. [18] Alternatively,c ross-coupling methodologies should allow access to am uch wider range of substituted azulenes.T he reactivity described above suggests Substitution at the azulene 1-and 3-positions has been most extensively explored, since these positions are the most reactive in S E Ar reactions.I nc ertain specific cases the desired substituent may be installed directly in one step by such an S E Ar process.…”
mentioning
confidence: 99%